Method for a Comprehensive Analytical Study of Contact Pressures, Wear, and Durability of Metal-Polymer Helical and Spur Gears with Steel Pinion and Polyamide Gear - Myron Czerniec; Marek Opielak; Jerzy Czerniec (Tribology in Industry, 2024)
An analytical complex study of metal-polymer (MP) helical and spur gears by a new author's analytical method was carried out. The influence of the helix angle on the contact pressures in the engagement, the teeth wear, and the durability of the MP gears of different polymers has been established. MP gears with a pinion made of carbon steel (0.45% C) and gear made of basic polyamides PA6, PA66, and their composites with the following fillers: fiberglass (PA6+30GF), carbon fiber (PA6+30CF), molybdenum disulfide (PA6+MoS2), and oil filled cast polyamide (PA6+Oil) are studied. According to the developed procedure for determination of the angles of engagement parity change, it is shown that there is two-one-two-pair or three-two-three-pair engagement depending on the helix angle. Quantitative and qualitative regularities of changes in the initial maximum contact pressures and their reduction due to tooth wear over the time from the moment of the entrance of teeth to engagement up to their exit from it are established. In particular, at a helix angle of β = 10°, the contact pressures reduce to 33% compared to spur gears. The linear wear of the gear polymer tooth profile at selected points of engagement and different helix angles has been investigated, and the influence of the pressure angle on it is shown. It is established that its regularities of change during the engagement phase are the same for all polymeric materials studied. The durability of transmissions is calculated, and its comparative evaluation is given. At the helix angle β = 5°, a slight increase in durability is achieved compared to spur gears, and at β = 10° the durability of MP gears increases by about 1.5 times for all polymeric materials studied.